In vitro activity of pineapple extracts (Ananas comosus, Bromeliaceae) on Rhipicephalus (Boophilus) microplus (Acari: Ixodidae) - Domingues, Luciana Ferreira [UNESP]; Giglioti, Rodrigo [UNESP]; Feitosa, Karina Alves; Fantatto, Rafaela Regina; Rabelo, Márcio Dias; Oliveira, Márcia Cristina de Sena; Oliveira, Gilson Pereira de [UNESP]; Bechara, Gervasio Henrique [UNESP]; Chagas, Ana Carolina de Souza (Elsevier, 2013)
Measures to control the cattle tick, Rhipicephalus (Boophilus) microplus, based only on chemical products are becoming unsustainable, mainly because of the development of resistance. The objective of this study was to test the effect of the aqueous extract of pineapple skin (AEPS) and bromelain extracted from the stem (Sigma-Aldrich®, B4882) on engorged females and larvae of R. (B.) microplus in vitro. These substances were diluted in water and evaluated at eight concentrations. Engorged females were collected and distributed in groups of 10, with three repetitions for each treatment. After immersion in the solutions, the females were placed in an incubator for observation of survival, oviposition and larval hatching. The larval packet method was used, also with three repetitions with about 100 larvae each. The packets were incubated and the readings were performed after 24h. The estimated reproduction and efficacy of the solutions were calculated. The LC50 and LC90 were estimated using the Probit procedure of the SAS program. The eight concentrations were compared within each treatment by the Tukey test. For the experiment with engorged females, the most effective concentrations were 125, 250 and 500mg/mL: 33%, 48% and 59% for the AEPS and 27%, 51% and 55% for the bromelain. The LC50 and LC90 values were, respectively, 276 and 8691mg/mL for AEPS and 373 and 5172mg/mL for bromelain. None of the dilutions tested was effective against the larvae of R. (B.) microplus. This is the first report of the action of pineapple extracts or their constituents on cattle ticks. The results demonstrate that further studies regarding composition of tick cuticle, with evaluation of other solvents and formulations, should be conducted seeking to enhance the effect of pineapple extracts and compounds against this ectoparasite. © 2013 Elsevier Inc.
Keywords: Botanical acaricides; Cattle tick; Industrial residue; Phytotherapy; Waste; Ananas comosus extract; bromelain; plant extract; unclassified drug; water; Acari; animal experiment; aqueous solution; Bromeliaceae; concentration response; controlled study; cuticle; dilution; drug screening; egg laying; female; hatching; immersion; in vitro study; insecticidal activity; Ixodidae; larval stage; LC 50; nonhuman; parasite survival; pineapple; plant stem; priority journal; reproduction; Rhipicephalus (Boophilus) microplus; Ananas; Animals; Bromelains; Cattle; Cattle Diseases; Female; Fruit; Larva; Lethal Dose 50; Plant Extracts; Rhipicephalus; Tick Control; Tick Infestations